A study of linguistic features indicated in lovers' parting politeness strategies in english versus vietnamese - Lê,Thị Nhung (2016)
There are different politeness strategies that are used to convey our communicative purposes. Without some these strategies, how can we use language effectively in different cultures? And it would be harder for us to be successful in cross-gender communication. In this paper, linguistic features indicated in politeness strategies used in expressing lovers' parting by different genders in English and Vietnamese is studied thoroughly with valuable contributions from sociolinguistics, pragmatics, semantics, syntax and cultural studies. This study is based on the theory of Face Study raised by Brown and Levinson as well as Politeness Principles of Leech in association with Social-Norm on Politeness. The basic view of this paper is that there are differences between men's and women's linguistic features indicated in verbal politeness strategies in expressing lovers’ parting and that these differences originate from different gender and cultures. Using the contrastive analysis of 200 samples from English and Vietnamese films, we could find that native English and Vietnamese speakers use three main politeness strategies ranging along a scale of increasing level of indirectness, namely Direct Strategy Category (DC), Conventionally Indirect Strategy Category (CI) and Non-Conventionally Indirect Strategy (NI). By analysing linguistic features in these different strategies, the research discovers the similarities and differences between them in the two languages. These differences can cause many difficulties in communication for English learners of Vietnamese and Vietnamese learners of English as a foreign language. We hope that the findings of this study could provide a deeper insight into the speech act of lovers’ parting in different cultures as well as help the interlocutors find an effective way in dealing with cross-gender communication. We also expect that this study could be a useful reference for other pragmatists.